Purification, Identification, and Properties of a Novel Carotenoid Produced by Arthrobacter sp. QL17 Isolated from Mount Qomolangma - Xue Yu; Kan Jiang; Wei Zhang; Shuqing Dong; Yujie Wu; Gaosen Zhang; Shiyu Wu; Tuo Chen; Guangxiu Liu (MDPI AG, 2022)
The genus Arthrobacter is a source of many natural products that are critical in the development of new medicines. Here, we isolated a novel carotenoid from Arthrobacter sp. QL17 and characterized its properties. The carotenoid was extracted with methanol, and purified by column chromatography and semi-preparative HPLC. Based on micrOTOF-Q and NMR analyses, the pigment was chemically characterized as 2,2'-((((1E,3E,5E,7E,9E,11E,13E,15E,17E,19E)-3,7,14,18-tetramethylicosa-1,3,5,7,9,11,13,15,17,19-decaene-1,20-diyl)bis(2,2,4-trimethylcyclohex-3-ene-3,1-diyl)) bis(ethan-2-yl-1-ylidene))bi(propane-1,3-diol), and named arthroxanthin. The biological activities of arthroxanthin were evaluated with DPPH, ABTS and MTT assays. Arthroxanthin exhibited excellent radical scavenging properties, as shown for 2, 20-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-n-(3,2-ethyl-benzothiazole-6-sulfonic acid) ammonium salt (ABTS), respectively, with IC50s of 69.8 and 21.5 µg/mL. It also showed moderate anticancer activities against HepG2, Hela, MDAB-231, SW480, and MKN-45 with IC50 values of 107.6, 150.4, 143.4, 195.9, and 145.5 μg/mL, respectively. Therefore, arthroxanthin derived from Arthrobacter sp. QL17 may be a potent antioxidant and anticancer agent for food and pharmaceutical use.